Photochemically active DNA-intercalating ruthenium and related complexes-insights by combining crystallography and transient spectroscopy - Kelly, John (My University, 2017)
Recent research on the study of the interaction of ruthenium polypyridyl compounds and defined sequence nucleic acids is reviewed. Particular emphasis is paid to complexes [Ru(LL)2(Int)]2+ containing potentially intercalating ligands (Int) such as dipyridophenazine (dppz), which are known to display light-switching or photo-oxidising behaviour, depending on the nature of the ancillary ligands. X-ray crystallography has made a key contribution to our understanding, and the first complete survey of structural results is presented. These include sequence, enantiomeric, substituent and structural specificities. The use of ultrafast transient spectroscopic methods to probe the ultrafast processes for complexes such as [Ru(TAP)2(dppz)]2+ and [Ru(phen)2(dppz)]2+ when bound to mixed sequence oligonucleotides are reviewed with particular attention being paid to the complementary advantages of transient (visible) absorption and time-resolved (mid) infra-red techniques to probe spectral changes in the metal complex and in the nucleic acid. The observed photophysical properties are considered in light of the structural information obtained from X-ray crystallography. In solution, metal complexes can be expected to bind at more than one DNA step, so that a perfect correlation of the photophysical properties and factors such as the orientation or penetration of the ligand into the intercalation pocket should not be expected. This difficulty can be obviated by carrying out TRIR studies in the crystals. Dppz complexes also undergo insertion, especially with mismatched sequences. Future areas for study such as those involving noncanonical forms of DNA, such as G-quadruplexes or i-motifs are also briefly considered
PUBLISHED
cited By 8
Keywords: Ruthenium polypyridyl compounds; Crystallography; Transient spectroscopy